2016
DOI: 10.1111/pin.12439
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of 49 primary gastrointestinal diffuse large B‐cell lymphoma cases; comparison with location, cell‐of‐origin, and frequency of MYD88 L265P

Abstract: The gastrointestinal (GI) tract is the most common primary site of extranodal diffuse large B-cell lymphoma (DLBCL), with approximately one-third of extranodal DLBCL occurring in the GI tract. We investigated the clinicopathological features and immunohistochemically-assessed cell-of-origin of 49 GI DLBCL cases (stomach, 24; small intestine, 10; colon, 15) and also examined the presence of MYD88 L265P as recently this mutation has been frequently identified in ABC-like DLBCL, particularly in extranodal sites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 21 publications
2
23
1
Order By: Relevance
“…Twenty-nine studies have reported that the frequency of MYD88 L265P mutation in 2285 DLBCL patients except for central nervous system (CNS) and testicular lymphomas was 16.5% (95% CI: 11.9–22.6%) 2, 3, 6, 7, 911, 13, 1622, 24, 25, 27, 28, 30, 31, 33–39, 41 . Thirteen 4, 5, 8, 9, 12, 14, 15, 18, 21, 23, 26, 32, 40 and four 8, 9, 21, 29 studies reported the prevalence of MYD88 L265P mutation in 378 CNS and 88 testicular DLBCL patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-nine studies have reported that the frequency of MYD88 L265P mutation in 2285 DLBCL patients except for central nervous system (CNS) and testicular lymphomas was 16.5% (95% CI: 11.9–22.6%) 2, 3, 6, 7, 911, 13, 1622, 24, 25, 27, 28, 30, 31, 33–39, 41 . Thirteen 4, 5, 8, 9, 12, 14, 15, 18, 21, 23, 26, 32, 40 and four 8, 9, 21, 29 studies reported the prevalence of MYD88 L265P mutation in 378 CNS and 88 testicular DLBCL patients.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies reported that MYD88 L265P mutation was detected in 255 (21%) of 1236 activated B-cell-like (ABC) or non-germinal center B-cell-like (non-GCB) subtype and in 44 (6%) of 766 GCB subtype patients 2, 6, 7, 9, 11, 16, 18, 21, 24, 25, 27, 30, 34, 36–39, 41 . The MYD88 L265P mutation was significantly associated with ABC or non-GCB subtype (OR = 3.414; 95% CI: 2.243–5.195; p < 0.001, Q = 19.986, I 2  = 14.865) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In one analysis, 33% of GI lymphomas were non-GCB, whereas MYD88 or CD79B mutations were identified in only <5% [86]. In an examination of 49 cases from Japan, the non-GCB phenotype was seen in 50%, but MYD88 mutation only in 6% [87]. Another series examining genetic profiles of GI DLBCL found only 3% rate of EZH2 Y641 mutation and 17% rate of BCL2 rearrangements in the GCB subgroup (none in the ABC subgroup), suggesting a low prevalence of the EZB genotype [88, 18].…”
Section: Prognosis Of Extranodal Dlbcl Arising From Specific Anatomicmentioning
confidence: 99%
“…Primary gastrointestinal DLBL generally expresses pan B-cell markers, such as CD19, CD20, CD22, CD79a, occasionally MUM-1+, and bcl-2+, and 50%-75% of cases express surface or cytoplasmic immunoglobulins [20,21]. In a study of 49 primary gastrointestinal DLBL cases, the histology and immunophenotyping showed that CD20+ and CD3-were the markers in all the cases [22]. On average, the Ki-67 labeling index was 68.3% (range, 35%-90%) and CD10 was positive in 44.9% of the cases, CD5 was positive in 4.1% of the cases, and c-MYC was positive in 23.4% of the cases [22].…”
Section: Discussionmentioning
confidence: 99%